Investigation of traction motor windings' insulation capacitance at switching frequencies under accelerated thermal stress - Panagiotou, P. A.; Gyftakis, K. N.; Lophitis, Neophytos; McCulloch, Mignon; Howey, D. A. (My University, 2017)
Machines in electric vehicles are driven by switching power electronic devices and undergo variable load cycling. In transient conditions high currents and temperatures develop, forcing the electric motor and particularly the insulation materials to undergo severe multi-stress. Insulation degradation will progressively lead to short-circuits which are harmful for the traction motor, vehicle safety and reliability. This paper focuses on the thermal assessment of insulation's capacitance at switching frequencies. For this, thin-film winding insulation samples were thermally aged at different temperatures and for various periods of time. Dielectric spectroscopy was applied and the capacitance information at different frequencies was extracted. The measurements were substituted to statistical analysis under three factors namely; ageing time, temperature and frequency. It is also evaluated how appropriate it is to use capacitance measurements as a means for reliable prognostics. The statistical analysis depicts that the capacitance does not follow predictable ageing patterns, mainly because the material's dielectric properties are affected by a number of different degradation mechanisms that occur concurrently.
Keywords: capacitance; degradation; dielectric spectroscopy; insulation; thermal stress; traction motor